ASHVAGANDHADHYA GHRITA-A CLASSICAL FORMULATION IN A NEW PERSPECTIVE PROPERTIES - Kothari, *Vasavdutta; Patgiri, B J; Prajapati, P K (International Journal of Ayurveda and Pharma Research, 2017)
Ashvagandha (Withania somnifera) is an important drug of Ayurvedic therapeutics. It is found almost all over India and the part used chiefly is root. This root smells like horses urine and so the name - Ashvagandha. Due to its multiple beneficial properties it is known as Indian ginseng. Somnifera in Latin means sleep inducing implicating its calming effect.Ashvagandhadhya Ghrita is a classical formulation stated in chapter of Vata Vyadhi in the text Chakradutta. It is prepared with ingredients- Ashvagandha Kvatha (decoction), Ashvagandha Kalka (paste), Go-dugdha and Go-ghrita. The individual ingredients of this formulation have Rasayan, Medhya etc. properties. Rasayan means that which promotes physical and mental health, helps to increase the bodys capacity to overcome diseases and diverse stress factors. It also enhances longetivity. Today, on similar line is concept of adaptogen- that which helps the body to face better the situations which produce stress and its related effects in body. Medhya means which is beneficial for intellect and memory.Moreover this is a formulation of Sneha Kalpana containing Ghrita as its base. It is known that blood brain barrier allows lipid soluble drugs to easily pass into the brain and thereby act on central nervous system.Thus looking to properties of individual ingredients and Kalpana (dosage form) it is hypothesized that the formulation as a whole also would have Rasayan i.e., adaptogenic and memory enhancing effect whereby it would be useful in conditions ranging from stress to anxiety to neurodegenerative diseases like Alzheimers disease etc.